Upaya Meningkatkan Pemahaman Siswa melalui Penggunaan Media Canva pada Mata Pelajaran Pendidikan Agama Islam (PAI) Kelas 4 SDN 04 Batang Anai - Annisa Aulia Putri; Nadia Afrina; Kasmaniar Kasmaniar; Khapipah Khapipah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Islamic Religious Education (PAI) plays an important role in shaping the morals and character of students. However, the learning process in grade IV of SDN 04 Batang Anai still faces obstacles in the form of low student interest and motivation because the methods used by teachers tend to be conventional. To overcome this, this study aims to improve student understanding by utilizing Canva as an interactive and interesting learning tool. This research is a Classroom Action Research (CAR) conducted in two cycles with stages of planning, implementation, observation, and reflection. The research subjects consisted of 15 fourth-grade students. Data were collected through observation, learning outcome tests, and documentation, then analyzed descriptively, quantitatively, and qualitatively. The results showed a significant increase in student learning outcomes. Classical mastery increased from 20% in the pre-cycle to 89% in cycle II. Student learning activities also improved significantly. Thus, the use of Canva media proved to be effective in improving student understanding and learning outcomes in Islamic Religious Education.